2019
DOI: 10.2147/ijn.s213942
|View full text |Cite
|
Sign up to set email alerts
|

<p>Analysis of toxicity and anticancer activity of micelles of sodium alginate-curcumin</p>

Abstract: BackgroundCurcumin is a natural polyphenol with anti-inflammatory, chemopreventive and anticancer activity. However, its high hydrophobicity and poor bioavailability limit its medical application. The development of nanocarriers for curcumin delivery is an attractive approach to overcome its low bioavailability and fast metabolism in the liver. We synthesized a blood compatible alginate-curcumin conjugate, AA-Cur, which formed colloidally stable micelles of approximately 200 nm and, as previously shown, exerte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…From this suspension, in which micellar structures form, curcumin can better be absorbed in the gastrointestinal tract. To overcome uptake limitations, a formulation of curcumin embedded in micelles on PEG80 basis was developed and shown to have superb uptake properties [ 21 , 22 , 23 , 42 , 43 , 44 , 45 ]. Micellar curcumin was recently also tested in a feeding study and demonstrated to be safe and effective as an anticancer agent in a colorectal mouse model [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…From this suspension, in which micellar structures form, curcumin can better be absorbed in the gastrointestinal tract. To overcome uptake limitations, a formulation of curcumin embedded in micelles on PEG80 basis was developed and shown to have superb uptake properties [ 21 , 22 , 23 , 42 , 43 , 44 , 45 ]. Micellar curcumin was recently also tested in a feeding study and demonstrated to be safe and effective as an anticancer agent in a colorectal mouse model [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The formulation was not toxic to mouse endothelial cells nor to cells isolated from human blood, but it showed strong cytotoxicity to various cancer cell lines. In the mice model, the formulation had no toxicity, but therapeutic effects were not as significant as those in vitro [117,118]. Dextran can also be used to form micelles.…”
Section: Polymeric Micellesmentioning
confidence: 94%
“…Unlike CCPs, hydrogels can be elongated or stretched under an external force to pass through narrower channels without clogging them, since they possess high plasticity determined by their softness [ 259 ]. Therefore, for intravenous injection an Alg-based drug delivery system can have a larger size than that of CCPs carriers; in this regard, some typical particles with sizes in the range of 180–400 nm have been investigated exhibiting good capabilities for carrying drugs [ 260 , 261 , 262 ]. However, that does not rule out a preference for smaller-sized Alg particles [ 263 , 264 , 265 ].…”
Section: Application Of Caco 3 and Alginate Carriersmentioning
confidence: 99%